Chances of Hungarian–Slovak Cross-Border Relations - Mezei, István (Discussion Papers, 2012)
The present paper deals with Hungary’s ’closest’ neighbour, Slovakia, with whom Hungary maintains the closest relations in the Carpathian Basin. After the Soviet control has ceased, Hungary might continue its thousand-year-old history, and the two nations might cooperate as equal partners and strive for better, more understanding and free countries, while fully recognising the inde¬pendence of the Slovak state that it gained in 1918. The paper attempts to take a snapshot of the historical ’moment’ after the accession. An important historical question arises for all accession countries and also for Slovakia: Will the differences between them and the Western European countries remain, or will these countries gradually become similar to each other? Will the centuries-long inequalities and development disparities between Western European and East-Central European countries ever cease? Besides the general question that refers to all accession countries there is another one that especially affects the two neighbouring countries, Hungary and Slovakia. How strong will the dividing role of borders be in the future? With political and economic frames becoming similar, and the borders ceasing, will their former economic and cultural relations revive? Will the regions that provide a potential framework for economic and social cooperation be formed on the basis of the real needs of their people? Will everyday human relations really be free? The present paper describes the international economic processes which forced a new kind of market mobility on the peoples in the Carpathian Basin and pushed the existing labour division into new political borders. This was supported by the Czech/Slovak policy, which, after 1920, created a rather closed kind of labour divi¬sion inside the new borders, in their own territories, excluding Hungary and other parts of the Carpathian Basin. Therefore the borderlands remain peripheries in both countries (and the Hungarian area along the Danube remains a dynamic connection with Western Europe without making the northern bank of the Danube its gravity zone). These peripheries will have to carry out development with the comparatively low sums of money that they may gain at tenders of regional development. In spite of such development they will never be able to achieve the degree of national dy¬namism. Consequently, much more moderate and controlled cross-border relations will mean the new form of cooperation.